2023
DOI: 10.1021/acs.analchem.3c00655
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Ordered Spectroscopy for Rapid and Facile Determination of Consumer Plastic Molecular Weight

Abstract: Molecular weight (MW) is a key control of plastic polymer properties and their fate in the environment. However, the primary tool used to determine plastic MW, gel permeation chromatography (GPC), has major limitations, such as low precision and accuracy, requirements for dedicated instrumentation, production of high volumes of hazardous waste, and large sample sizes. In this study, we describe, validate, and apply a diffusion-ordered spectroscopy (DOSY) method for polymer MW determinations, with a focus on ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In our previous work, we had used 298 K (25 °C), yet others would have chosen any temperature around room temperature. Hence, we tested the outcome of the calibration for polystyrene (probably, to date, the best tested polymer for DOSY calibrations 8,10,17–23 ) in the temperature range of 273 to 313 K (0 to 40 °C) using the exact same methodology as earlier.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous work, we had used 298 K (25 °C), yet others would have chosen any temperature around room temperature. Hence, we tested the outcome of the calibration for polystyrene (probably, to date, the best tested polymer for DOSY calibrations 8,10,17–23 ) in the temperature range of 273 to 313 K (0 to 40 °C) using the exact same methodology as earlier.…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, the data discussed above suggest a methodology or instrument dependence. Usually, the so-called Longitudinal Eddy-current Delay Bipolar Gradient Pulse (ledbpgp2s) program 27 is largely used in the molar mass estimation of polymers 10,14,16,22,28 because it is possible to get optimised results in lower gradient strength pulses, 29 which can be essential for performing DOSY on macromolecules. We found that by applying this sequence, using the ledbpgp2s program, significant temperature deviations occur at the extremes of the temperature range studied, 273 and 313 K, despite care being taken to ensure the samples had sufficient time to thermally equilibrate, with the measurement undertaken at a high gas flow rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though size exclusion chromatography (SEC) is, by far, the most used technique to characterize polymer molecular weight and molecular weight distribution, it still has some limitations [65]. In addition, some recent studies [77] have highlighted the potential use of DOSY for molecular weight analysis of a variety of consumer plastic products. DOSY is an NMR method that reports diffusion coefficients (D) for individual resonances in the NMR spectra.…”
Section: Characterization By Nuclear Magnetic Resonance (Nmr): Diffus...mentioning
confidence: 99%
“…An attractive example is the use of DOSY which is routinely being used with relatively expensive and difficult‐to‐access high‐field NMR which requires cryogenic magnets. [ 4,5 ]…”
Section: Introductionmentioning
confidence: 99%